Congenital myasthenic syndrome due to rapsyn deficiency: A case report with a new mutation and compound heterozygosity - Espinoza, Ivan O. (Medwave, 2019)
INTRODUCTION: The congenital myasthenic syndromes are a heterogeneous group of genetic disorders characterized by an abnormal synaptic transmission at the neuromuscular junction. REPORT: We present a two-year old patient, male, with hypotonia, palpebral ptosis and proximal symmetric weakness with neonatal onset that required several and prolonged hospitalizations for pneumonia and respiratory failure. From two years of age, the parents noticed that the facial and general weakness worsened in the afternoons and with repeated or prolonged physical activity. The physical examination showed palpebral ptosis, predominantly proximal weakness and fatigability with sustained muscular effort. The electromyogram showed a 27% decrement of the compound muscle action potential. Genetic study of the patient’s parents revealed compound heterozygosity with transmission of two different mutations in the rapsyn gene from both parents. The patient received pyridostigmine with great improvement, achieving optimal performance in school, sports, and daily life activities. CONCLUSIONS: Weakness and fatigability with neonatal onset, mainly affecting the muscles with brain stem innervation and the decrement greater than 10 percent in the Compound Muscular Action Potential in the electromyographic studies, should make us suspect in a congenital myasthenic syndrome. We review the literature and key clinical points to stablish opportune diagnosis and effective treatment in some of these syndromes.